Hubungan Pemberian Anestesi Regional Dengan Kelancaran ASI Pada Ibu Post Partum Sectio Caesarea Di Rumah Sakit Muhammadiyah Gresik - Rahmatika, Vina; Ghufron, Musa; Triastuti, Nenny; Rochman, Syaiful (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2020)
The Relationship between Regional Anesthesia and Breastfeeding Smoothness in Post Partum Sectio Caesarea Mothers at Muhammadiyah Hospital GresikBackground: The birth rate by caesarean section method is getting higher. Risk data for 2013 shows the method of birth with the operation method of 9.8 percent of the total 49,603 births during 2010 to 2013. Being in practice the mother must be given anesthetic before the surgery begins. This anesthesia will later affect the pain that will occur after SC.Objective: The purpose of this study was to determine the correlation between regional anesthetic drugs and the smoothness of breast milk in women born in sectio caesarea at Muhammadiyah Gresik Hospital.Method: Method with Cross Sectional approach. The population in this study mothers who gave birth in a caesarean section at Muhammadiyah Hospital Gresik in December 2019 to January 2020. The sampling technique in this study is probability / random simple sampling. The sample in this study was a portion of mothers who gave birth in a caesarean section at Muhammadiyah Gresik Hospital. The instrument used was primary data collection in the form of questionnaires and secondary data in the form of patient medical records.Result: The data obtained in this study were processed using spearman correlation statistics. From the statistical test the Correlation coefficient value was 0.807, and obtained P-Value equal to 0,000 this value is less than 0.05.Conclusion: The conclusion of this study is that there is a correlation between the administration of a regional anesthetics and the smoothness of breast milk in mothers of post partum caesarea at Muhammadiyah Gresik Hospital.